The use of microRNAs as cervical cancer biomarkers (Research, Society and Development, 2022)
This work aimed to describe the role of miRNAs in the gene regulation of cervical cancer. For this integrative literature review, articles found in the PubMed, SciELO, Lilacs and Sciencedirect databases were used, selecting works published between 2011 and 2021, in Portuguese and English, considering the following descriptors: “microRNAs”, “regulation of gene expression”, “cervical cancer” and “biomarkers”. A total of 156 works were found, and finally, 17 works were selected for study. Studies have pointed to a direct relationship between miRNAs and the stages of development of cervical cancer. Several miRNAs, such as miR-21 and miR-135a, have their expression increased in cervical cancer cells when compared to their levels in normal individuals. Other miRNAs, such as miRNA-20a, miR-1246, miR-2392, miR-3147, miR-3162-5p and miR-4484, have been identified as promising biomarkers for the detection of metastasis in patients with cervical cancer. Variation in the expression levels of miRNAs, on the other hand, can interfere with sensitivity to chemotherapy, such as miR-155, which increases chemosensitivity to cisplatin, an antineoplastic agent. Thus, the analysis of miRNA signatures in patients such as cervical cancer appears as a promising tool for its diagnosis, prognosis and treatment, requiring their association with the usual methods for a better clinical management.